Syntax of Dutch: Adpositions and Adpositional Phrases - Broekhuis, Hans (Comprehensive Grammar Resources, 2013)
The volume Adpositions and Adpositional Phrases discusses the internal make-up and the distribution of adpositional phrases. Topics that are covered include complementation and modification of adpositional phrases, as well as their predicative, attributive and adverbial uses. A separate chapter is devoted to the formation and the syntactic behavior of pronominal PPs like erop 'on it', which also includes a more general discussion of the syntax of so-called R-words like er 'there'.